2021
DOI: 10.1111/aej.12597
|View full text |Cite
|
Sign up to set email alerts
|

Malignant tumours mimicking periapical lesions: A report of three cases and literature review

Abstract: Apical periodontitis shows radiographic signs such as widening of the periodontal ligament and periapical radiolucency, which differ in extent depending on the stage of the lesion. However, other lesions can be associated with or coincidental to the apical region, representing developmental lesions and benign or malignant tumours. This article describes three cases of malignant tumours, a central mucoepidermoid carcinoma (CMEC), a chondroblast osteosarcoma and an osteosarcoma of the jaw (OSJ) that presented as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Evangelista et al. (2022) emphasized that endodontists should be aware of unsuccessful treatments, rapid growth rates or a delayed response to treatment. They concluded that complementary examinations, such as biopsy and computed tomography, would allow early diagnosis of malignant tumours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evangelista et al. (2022) emphasized that endodontists should be aware of unsuccessful treatments, rapid growth rates or a delayed response to treatment. They concluded that complementary examinations, such as biopsy and computed tomography, would allow early diagnosis of malignant tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Ortega et al (2007) that lesions should be studied histopathologically, especially large lesions, because they could be odontogenic tumours, such as ameloblastoma or malignant lesions. Evangelista et al (2022) emphasized that endodontists should be aware of unsuccessful treatments, rapid growth rates or a delayed response to treatment. They concluded that complementary examinations, such as biopsy and computed tomography, would allow early diagnosis of malignant tumours.…”
Section: Discussionmentioning
confidence: 99%